2008
DOI: 10.1007/s10157-008-0053-6
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic collapsing glomerulopathy in children

Abstract: Collapsing glomerulopathy is an aggressive variant of focal segmental glomerulosclerosis. All patients with CG should be screened for the underlying etiology, and patients with idiopathic CG should be offered a trial of immunosuppressive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 19 publications
4
21
0
Order By: Relevance
“…Collapsing FSGS has been described by many authors from different parts of the world as a cause of SRNS in children [9,12,13,14]. Our patient had high blood pressure at presentation, and this is similar to previous reports of initial high blood pressure in affected children [13].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Collapsing FSGS has been described by many authors from different parts of the world as a cause of SRNS in children [9,12,13,14]. Our patient had high blood pressure at presentation, and this is similar to previous reports of initial high blood pressure in affected children [13].…”
Section: Discussionsupporting
confidence: 79%
“…In general, there is a poor response to steroids [12,13,14]. However, remission is achievable in some patients with other immunosuppressive therapy [14,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…These studies have established this pattern of glomerular injury as a clinically and pathologically distinct variant of FSGS and not as a separate clinicopathologic entity [18][19][20][21][22][23][24][25][26][27][28]. All the later studies have reported a similar rapidly progressive course to renal failure in patients with collapsing FSGS who lack HIV-1 infection [18][19][20][21][22][23][24][25][26][27][28]. Collapsing FSGS is less commonly reported from Europe [20,21] and only occasional cases are reported from tropical countries [27,28].…”
Section: Discussionmentioning
confidence: 96%
“…Since then, Fibrointimal thickening of arteries a 1 1 5 6 9 2 2 0 2 3 -2 2 1 1 3 22 3 19 3 2 0 4 5 -1 3 1 0 5 27 -11 2 1 1 6 16 -13 a number of studies on this lesion have appeared in the medical literature, mostly from the United States, predominantly in the form of case reports or small series [17][18][19][20][21][22][23][24][25][26][27][28]. These studies have established this pattern of glomerular injury as a clinically and pathologically distinct variant of FSGS and not as a separate clinicopathologic entity [18][19][20][21][22][23][24][25][26][27][28]. All the later studies have reported a similar rapidly progressive course to renal failure in patients with collapsing FSGS who lack HIV-1 infection [18][19][20][21][22][23][24]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation